Asymmetric adhesive biological patch as well as preparation method and application thereof
By combining SIS, PAA, vancomycin and magnesium ions, an asymmetrically adherent biological patch was developed, which solved the shortcomings of existing dura repair materials in biocompatibility, antibacteriality and pro-angiogenesis, and achieved more effective dura repair effects.
Patent Information
- Application Number
- CN202411810772.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
AI Technical Summary
Existing dura repair materials have problems with biocompatibility, mechanical integrity and prevention of cerebrospinal fluid leakage. At the same time, the exposed dura is susceptible to bacterial infection and requires antibacterial properties to prevent postoperative infection.
Asymmetrically adherent biological patch was developed to form a multifunctional repair biological patch with biocompatible, antibacterial and proangiogenic properties by combining biocompatible submucosal layer of pig small intestinal (SIS), adhesion polyacrylic acid (PAA), vancomycin and proangiogenic magnesium ions.
This biological patch can effectively block cerebrospinal fluid leakage, release vancomycin and magnesium ions, promote tissue regeneration and angiogenesis, and significantly improve the clinical effect of dura repair.
Smart Images

Figure CN119587751A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an asymmetric adhesive biological patch and a preparation method and application thereof, belonging to the field of biomedical materials. Background Art
[0002] The dura mater is a tough, protective membrane that wraps around the brain and spinal cord and plays a key role in maintaining the integrity and function of the central nervous system. Dural tears occur in approximately 20% of craniotomies, significantly increasing the risk of local and systemic postoperative complications. In the United States, the average surgical cost of repairing dural tears is $18,499 per patient per year, and this figure continues to rise. Clinically, dural injuries may be caused by trauma, tumor resection, cerebrovascular intervention, or craniotomy. Such injuries not only predispose patients to cerebrospinal fluid (CSF) leakage, but also increase the risk of serious complications, including intracranial infection and brain herniation, which negatively affects the patient's prognosis and quality of life. Therefore, effective dura mater repair techniques are essential in clinical practice.
[0003] Traditional dura mater repair strategies include autologous dura mater or fascia, allogeneic dura mater, and synthetic materials. However, these methods have some challenges, such as complications at the donor site, immune rejection of allogeneic grafts, and problems with synthetic materials in terms of biocompatibility, mechanical integrity, and prevention of CSF leakage. In addition, during craniotomy, the exposed dura mater is susceptible to bacterial infection, which requires the repair material to have antibacterial properties to prevent postoperative infection. At the same time, the repair material should promote angiogenesis to promote wound healing and prevent long-term CSF leakage and other complications. Therefore, the development of dura mater repair materials that are both biocompatible, antibacterial, and pro-angiogenic has become a focus of tissue engineering and regenerative medicine research.
[0004] The main methods for dura mater repair include autologous tissue transplantation, allogeneic tissue transplantation, and synthetic materials. Autologous transplantation uses the patient's own dura mater or fascia, which is favored because it is easy to obtain and has no immune rejection reaction. However, this method requires additional surgery, resulting in secondary trauma and functional loss of the donor site. Allogeneic transplantation uses the donor's dura mater or other biological materials, avoiding the need for additional surgery, but there is a risk of immune rejection and disease transmission, which limits its clinical application. Synthetic materials such as polyvinyl alcohol and polytetrafluoroethylene can provide good mechanical strength and plasticity to form an immediate physical barrier. However, these materials usually have poor biocompatibility and lead to chronic inflammation. In addition, they lack antibacterial properties and are difficult to effectively prevent postoperative infection. Synthetic materials usually do not have the function of promoting tissue regeneration or angiogenesis, resulting in poor repair effects. In recent years, the application of porcine small intestinal submucosa (SIS) extracellular matrix materials in dura mater repair has gradually attracted attention. Porcine SIS is derived from decellularized porcine tissue, retains important extracellular matrix structures and components, and has excellent biocompatibility and biodegradability. It provides a carrier for cell proliferation and tissue regeneration, promotes the formation of new tissue and supports functional recovery. In dura repair, SIS provides mechanical stability and promotes angiogenesis and healing due to its natural composition. However, the antibacterial and adhesion properties of SIS are limited, which hinders its effectiveness in preventing postoperative infection and CSF leakage. Therefore, the development of a modified SIS material with integrated antibacterial, adhesion and pro-angiogenic functions has become the focus of current research. Summary of the invention
[0005] Problem that the invention aims to solve
[0006] Traditional dura mater repair strategies include autologous dura mater or fascia, allogeneic dura mater, and synthetic materials. However, these methods have some challenges, such as donor site complications, immune rejection of allogeneic grafts, and problems with synthetic materials in terms of biocompatibility, mechanical integrity, and prevention of CSF leakage. In addition, during craniotomy, the exposed dura mater is susceptible to bacterial infection, and the repair material needs to have antibacterial properties to prevent postoperative infection. At the same time, the repair material should promote angiogenesis to promote wound healing and prevent long-term CSF leakage and other complications.
[0007] The present disclosure provides an asymmetric adhesive biological patch, which forms a multifunctional repair biological patch by combining biocompatible SIS, adhesive polyacrylic acid (PAA), vancomycin and pro-angiogenic magnesium ions. The asymmetric adhesive biological patch has biocompatibility, antibacterial and pro-angiogenic properties, and its use in dura mater repair materials can provide more effective effects for tissue repair.
[0008] The present disclosure also provides a method for preparing an asymmetric adhesive biological patch, which is simple and easy to implement, and the raw materials are easy to obtain, and is suitable for mass production.
[0009] Solutions for solving problems
[0010] [1] An asymmetric adhesive biological patch, comprising:
[0011] A substrate having a fiber structure, and
[0012] An adhesive layer, the adhesive layer is derived from an adhesive composition, the adhesive composition includes a monomer, a photoinitiator and a crosslinking agent, and,
[0013] The adhesive composition further comprises an antibiotic compound and / or a component providing active metal ions.
[0014] [2] According to the asymmetric adhesive biological patch described in [1], based on the total weight of the adhesive composition being 100%, the content of the antibiotic compound is 0.1%-3%, and / or the content of the component providing active metal ions is 1%-10%.
[0015] [3] The asymmetric adhesive biopatch according to [1] or [2], wherein the active metal ions include one or a combination of two or more of magnesium ions, copper ions, calcium ions, manganese ions, zinc ions, chromium ions, cobalt ions, strontium ions, and iron ions; and / or
[0016] The antibiotic compound includes one or a combination of two or more of penicillins, cephalosporins, erythromycin, lincomycin, clindamycin and vancomycin.
[0017] [4] The asymmetric adhesive biopatch according to any one of [1] to [3], wherein the content of the monomer is 70%-97%, the content of the photoinitiator is 0.2%-5%, and the content of the crosslinker is 1%-10%, based on the total weight of the adhesive composition being 100%.
[0018] [5] The asymmetric adhesive biological patch according to any one of [1] to [4], wherein the monomer comprises an acrylic monomer and / or an acrylamide monomer; preferably comprises one or a combination of two or more of acrylic acid, polyacrylamide, polyacrylic acid, and poly(hydroxyethyl methacrylate); and / or
[0019] The cross-linking agent includes one or a combination of two or more of methacrylated gelatin, methacrylated hyaluronic acid, polycaprolactone diacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and N,N-methylenebisacrylamide; and / or,
[0020] The photoinitiator includes a ketone photoinitiator, preferably including one or a combination of two or more of α-ketoglutaric acid, 2,2-dimethoxy-2-phenylacetophenone, α-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0021] [6] The method for preparing the asymmetric adhesive biological patch described in any one of [1] to [5] comprises the step of composite-molding the adhesive layer and the substrate.
[0022] [7] The preparation method according to [6], comprising the following steps:
[0023] a step of obtaining an adhesive composition;
[0024] The adhesive composition is present on at least one surface of the substrate, and an asymmetric adhesive biological patch is obtained after chemical reaction.
[0025] [8] According to the preparation method described in [6] or [7], the adhesive composition is dissolved in a solvent to form a prepolymer solution, and the prepolymer solution is present on at least one surface of the substrate.
[0026] [9] According to any one of [6] to [8], the reaction conditions include being carried out under ultraviolet light irradiation; preferably, the power of the ultraviolet light is 200-400 W, and the irradiation time is 25-40 minutes.
[0027]
[10] Use of the asymmetric adhesive biological patch according to any one of [1] to [5] for preparing tissue repair products, in particular for preparing dura mater repair materials, skull repair materials, and post-operative defect repair materials.
[0028] Effects of the Invention
[0029] In the present disclosure, an asymmetric adhesive biological patch is designed, which has antibacterial and pro-angiogenic properties. It is a multifunctional tissue repair biological patch that provides a new option for improving the clinical effect of tissue repair, especially has great potential in the clinical application of dura mater repair.
[0030] Furthermore, compared with using adhesive alone, the asymmetric adhesive biological patch (only one side is adhesive) provided by the present invention can significantly reduce tissue adhesion when used in vivo, because when adhesive is used alone, after one side adheres to the wound surface, the exposed other side may contact other organs, resulting in more obvious adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram showing the preparation and characterization of an asymmetric adhesive biopatch.
[0032] Figure 1 a in the figure is a schematic diagram of the preparation method: vancomycin and magnesium carbonate are first added to an acrylic acid solution, and then the solution is coated on the SIS patch and cross-linked by ultraviolet light; Figure 1 b is the general appearance of the SIS / PAA / Van@Mg biological patch and its potential laparoscopic application; Figure 1 c in the figure is the infrared spectra of vancomycin, SIS / PAA and SIS / PAA / Van biological patch; Figure 1 Figure d in the figure is the cross-sectional scanning electron microscope image of the SIS / PAA / Van@Mg biopatch and the elemental surface scan of magnesium.
[0033] Figure 2 The results showing the cumulative release of SIS / PAA / Van@Mg biopatch immersed at 37°C.
[0034] Figure 2 a in the figure shows the result of cumulative release of vancomycin; Figure 2 Panel b shows the result of cumulative release of magnesium ions.
[0035] Figure 3 Results of tissue adhesion experiments showing an asymmetric adhesive biological patch.
[0036] Figure 3 ac in the figure respectively show the bursting strength, shear bond strength, and interface toughness based on ASTM F2392, ASTM F2255, and ASTM F2256 test standards; Figure 3 (d) shows the adhesion of SIS / PAA / Van@Mg biopatch to different tissues; Figure 3 The figure e shows the performance comparison with the current biological adhesives used for dura mater repair. The stars in the figure represent the biological patches disclosed in the present invention, and the circles represent the current tissue adhesives. The P value was compared using the variance analysis test, and the data were expressed as mean ± standard deviation (n = 4). The difference was statistically significant. *** P≤0.001.
[0037] Figure 4 Results showing the cytocompatibility of the asymmetric biopatch.
[0038] Figure 4 a in the figure is the result of hemolysis experiment, and the color of the supernatant can be seen in the inset; Figure 4 b in the figure is the result of L929 cell toxicity of the extract of the biological patch; Figure 4c in the figure is the result of live and dead cell staining of the extract. P value was compared by variance analysis, and the data were expressed as mean ± standard deviation (n = 4), and there was no statistically significant difference.
[0039] Figure 5 Showing the results of antibacterial experiments on asymmetric adhesive biopatch.
[0040] Figure 5 a in the figure is the morphology of S. aureus on different biological patches; Figure 5 b in the figure is the result of inhibition zone of different biological patches; Figure 5 c in the figure is the result of antibacterial rate of different biological patches; Figure 5 Figure d in the figure shows the results of crystal violet staining of different biological patches; Figure 5 e in the figure is the quantitative analysis result of crystal violet staining of different biological patches. P value was compared by analysis of variance, and the data were expressed as mean ± standard deviation (n = 3). The difference was statistically significant. ** P≤0.01, *** P≤0.001.
[0041] Figure 6 Showing the results of the vascularization viability test of the asymmetric adhesive biopatch.
[0042] Figure 6 a in the figure is the result of scratch assay of HUVECs to evaluate the cell migration level; Figure 6 b is the result of tube formation experiment on Matrigel; Figure 6 c in the figure is the result of VEGF immunofluorescence staining; Figure 6 The d in the figure is the result of semi-quantitative analysis of statistical migration distance; Figure 6 e in the figure is the result of semi-quantitative analysis of microtubule length; Figure 6 f in the figure is the result of semi-quantitative analysis of VEGF fluorescence intensity. P value was compared by analysis of variance, and the data were expressed as mean ± standard deviation (n = 3). The difference was statistically significant. * P≤0.05, *** P≤0.001.
[0043] Figure 7 Shown are the results of an asymmetric adhesive biological patch applied to infected rat dura mater lesions.
[0044] Figure 7 Figure a is the animal experiment flow chart: first, dura mater injury is established, then exogenous S. aureus is introduced to simulate infection, and then the biological patch is implanted to treat bacterial inflammation; Figure 7 b shows the results of colony formation, H&E staining, Giemsa staining, and immunofluorescence staining 1 week after surgery; Figure 7c in the figure shows the results of H&E staining and immunofluorescence staining 4 weeks after surgery; Figure 7 The d in the figure is the result of semi-quantitative analysis of the number of colonies, TNF-α and CD163 fluorescence intensity. The P value was compared using analysis of variance, and the data were expressed as mean ± standard deviation (n = 4). The differences were statistically significant. * P≤0.05, ** P≤0.01, *** P≤0.001.
[0045] Figure 8 Shown are the results of an asymmetric adhesive biological patch used to repair dura mater injuries in rabbits.
[0046] Figure 8 Figure a is a flowchart of animal experiments: first, a dura mater injury model is established, and then different biological patches are implanted to promote wound repair; Figure 8 b in the figure represents 2 weeks after surgery and Figure 8 c in the figure are H&E staining and Masson's trichrome staining 4 weeks after surgery; Figure 8 The d in the figure are the results of evaluating the collagen production level 2 and 4 weeks after surgery; Figure 8 e in the figure shows the results of VEGF immunofluorescence staining at 2 and 4 weeks after surgery; Figure 8 f in the figure is the result of semi-quantitative statistical analysis of VEGF fluorescence intensity at 2 weeks and 4 weeks after surgery. P value was compared by analysis of variance, and the data were expressed as mean ± standard deviation (n = 3). The difference was statistically significant. * P≤0.05, ** P≤0.01, *** P≤0.001.
[0047] Fig. 9 The results of immunofluorescence staining of the rabbit dura mater injury model at 2 and 4 weeks after surgery are shown.
[0048] Fig. 9 a and Fig. 9 b in the figure are the results of immunofluorescence staining at 2 and 4 weeks after surgery; Fig. 9 c in the figure is the result of semi-quantitative statistical analysis of the fluorescence intensity of TNF-α, TGF-β and VEGF. The P value was compared by analysis of variance, and the data were expressed as mean ± standard deviation (n = 3). The difference was statistically significant. * P≤0.05, ** P≤0.01, *** P≤0.001.
[0049] Fig.10 Shows the results of pathological staining of heart, liver, spleen, lung, and kidney tissues in a rabbit dura mater injury model 4 weeks after surgery.
[0050] Fig.11 Shown are the results of hematological examination 4 weeks after surgery in the rabbit dura mater injury model.
[0051] Fig.11 a in the figure is the blood routine test of the rabbit dura mater injury model 4 weeks after surgery; Fig.11 Panel b shows the serum biochemical test of the rabbit dura mater injury model 4 weeks after surgery.
[0052] Fig.12 Showing the results of an asymmetric adhesive biopatch applied to a beagle dog dura mater injury model.
[0053] Fig.12 Figure a is a flowchart of animal experiments: first, a dura mater injury model is established, and then different biological patches are implanted to promote wound repair; Fig.12 b is the ECG curve of the SIS / PAA / Van@Mg biopatch implanted in vivo; Fig.12 c in the figure shows the results of collagen production and vascularization levels 8 weeks after surgery; Fig.12 Figure d in the figure is the result of Masson's trichrome staining 8 weeks after surgery; Fig.12 e in the figure is the result of immunofluorescence staining 8 weeks after surgery. P value was compared by analysis of variance, and the data were expressed as mean ± standard deviation (n = 3). The difference was statistically significant. ** P≤0.01, *** P≤0.001.
[0054] Fig.13 Shown are the results of immunofluorescence staining in the beagle dog dura mater injury model 8 weeks after surgery.
[0055] Fig.14 Shown are the results of pathological staining of heart, liver, spleen, lung, and kidney tissues in the beagle dog dura mater injury model 8 weeks after surgery.
[0056] Fig.15 Schematic diagram showing the preparation and application of the biological patch.
[0057] Fig.15 Figure a is a schematic diagram of the preparation of the biological patch: the acrylic acid prepolymer solution is mixed with the biologically active components magnesium carbonate (MgCO3) and vancomycin, and then coated on the surface of the SIS biological patch. After UV cross-linking, an asymmetric adhesive biological patch is successfully prepared; Fig.15 b is a schematic diagram of the application of biological patches: when applied to dura mater injuries, the asymmetric adhesive biological patch can block cerebrospinal fluid leakage and release vancomycin and magnesium ions (Mg 2+ ), promoting tissue regeneration. DETAILED DESCRIPTION
[0058] Various exemplary embodiments, features and aspects of the present disclosure will be described in detail below. The word "exemplary" used herein means "used as an example, embodiment or illustrative". Any embodiment described herein as "exemplary" is not necessarily to be interpreted as being superior or better than other embodiments.
[0059] In addition, in order to better illustrate the present disclosure, numerous specific details are given in the following specific embodiments. It should be understood by those skilled in the art that the present disclosure can also be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present disclosure.
[0060] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in this disclosure should be understood to include the inevitable systematic errors in industrial production.
[0061] In this specification, the word "may" includes both performing a certain process and not performing a certain process.
[0062] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0063] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0064] As used in this disclosure, "HUVECs" means Human Umbilical Vein Endothelial Cells.
[0065] As used in this disclosure, "L929 cells" refers to mouse fibroblast cells (L929 cells).
[0066] As used in this disclosure, "VEGF" stands for Vascular Endothelial Growth Factor.
[0067] As used in this disclosure, "TNF-α" means Tumor Necrosis Factor-α.
[0068] As used in this disclosure, "CD163" means scavenger receptor type B (Cluster of Differentiation 163).
[0069] As used in this disclosure, "TGF-β" stands for Transforming Growth Factor-β.
[0070] As used in this disclosure, "TLR2" means Toll-Like Receptor 2.
[0071] As used in the present disclosure, "CD4" refers to a cytokine on the surface of T cells (Recombinant Cluster of Differentiation 4).
[0072] As used in this disclosure, "FGF" stands for Fibroblast Growth Factor.
[0073] As used in this disclosure, "F-actin" means fibrous actin.
[0074] <First aspect>
[0075] A first aspect of the present disclosure provides an asymmetric adhesive biological patch, comprising:
[0076] A substrate having a fiber structure, and
[0077] The adhesive layer is derived from an adhesive composition, wherein the adhesive composition comprises a monomer, a photoinitiator and a cross-linking agent, and the adhesive composition further comprises an antibiotic compound and / or a component providing active metal ions.
[0078] The asymmetric adhesive biological patch disclosed in the present invention has excellent bursting strength, strong tissue adhesion and sustained drug release ability, superior antibacterial properties, effective CSF sealing effect and enhanced tissue regeneration ability, thereby producing a significant tissue repair effect.
[0079] <Base>
[0080] The matrix disclosed in the present invention is a matrix with a fiber structure. The present invention does not specifically limit the matrix, and it can be some commonly used matrixes in the art. In the present invention, the matrix is derived from a biodegradable biomaterial, preferably a biomaterial mainly containing collagen, and the collagen can be of natural origin, artificial synthesis, modified or cross-linked, including but not limited to submucosal layer, dermis, pericardium, collagen, gelatin, etc.
[0081] In some embodiments of the present disclosure, the matrix is derived from SIS, preferably from decellularized SIS, that is, the matrix of the present disclosure can be prepared using SIS. In some embodiments of the present disclosure, the matrix is derived from the dermis, preferably from the decellularized dermis, that is, the matrix of the present disclosure can be prepared using the dermis. In some embodiments of the present disclosure, the matrix is derived from the bladder submucosa, preferably from the decellularized bladder submucosa, that is, the matrix of the present disclosure can be prepared using the bladder submucosa. In some embodiments of the present disclosure, the matrix is derived from the pericardium, preferably from the decellularized pericardium, that is, the matrix of the present disclosure can be prepared using the pericardium. The submucosa (such as SIS), dermis and pericardium, etc. are preferably derived from mammals, such as pigs, cattle, sheep, dogs, cats, etc.
[0082] In one embodiment of the present disclosure, the matrix is derived from decellularized porcine SIS. The porcine SIS can be purchased commercially. Porcine SIS is widely available, economical and easy to obtain, and easy to process. The decellularized porcine SIS has excellent biocompatibility, is rich in collagen and growth factors, can induce cells to diffuse, adhere, grow, and proliferate inward, and promote the repair and regeneration of the tissue defect's own tissue. It is suitable for use as a matrix for preparing the biological patch of the present disclosure. Therefore, the present disclosure preferably uses the porcine SIS material matrix prepared as a raw material as a matrix.
[0083] The present disclosure does not specifically limit the preparation method of the porcine SIS material matrix, which may be some commonly used preparation methods in the art, and the porcine SIS material matrix may also be purchased commercially. Preferably, the porcine SIS material matrix of the present disclosure may be prepared according to the preparation method in CN107007886A.
[0084] In another embodiment of the present disclosure, the substrate may also be a fiber membrane prepared by using a chemical substance containing collagen. The present disclosure does not specifically limit the fiber membrane, and it may be a fiber membrane commonly used in the art, such as a non-woven fiber membrane or a spun fiber membrane.
[0085] The nonwoven fiber membrane of the present disclosure can be obtained by nonwoven process using a chemical substance containing collagen and one or more combinations of other polymers or their derivatives that are optionally present. The spun fiber membrane of the present disclosure can be obtained by electrostatic spinning technology, centrifugal spinning technology, hot melt spinning technology, melt electrospinning technology, etc. using a chemical substance containing collagen and one or more combinations of other polymers or their derivatives that are optionally present.
[0086] Other high molecular polymers or their derivatives may be various commonly used high molecular polymers or their derivatives in the art, such as one or a combination of two or more selected from natural high molecular polymers. For example, commonly used high molecular polymers or their derivatives may be one or a combination of two or more selected from cellulose, chondroitin sulfate, chitosan, modified chitosan, fibrin, silk protein, elastin-mimicking peptide polymers, heparin, agar, dextran, alginic acid, cellulose, alginic acid, and starch.
[0087] Preferably, in order to obtain an asymmetric adhesive biological patch with excellent performance in all aspects, the present disclosure preferably uses a porcine SIS material matrix. Based on the matrix of the present disclosure, the biological patch of the present disclosure contains collagen fibers, and due to the presence of collagen fibers, the asymmetric adhesive biological patch of the present disclosure can better play its role.
[0088] <Adhesive Layer>
[0089] The adhesive layer disclosed in the present invention has strong adhesive force and can be used for preparing tissue repair products, especially for preparing dura mater repair products. For example, in dura mater repair, the adhesive layer can effectively seal the wound and prevent CSF leakage, and at the same time, due to its good biocompatibility, it can reduce inflammatory response.
[0090] Adhesive composition
[0091] The adhesive layer of the present disclosure is derived from an adhesive composition including a monomer, a photoinitiator, and a cross-linking agent.
[0092] In the present disclosure, the monomer contains active groups, such as carboxyl groups, and the active groups can form tissue adhesion with the tissue surface through physical forces such as hydrogen bonds and electrostatic interactions in a short period of time. As the contact time increases, the active groups undergo amidation reaction with the amino groups on the tissue surface to form chemical bonds, thereby achieving tissue adhesion.
[0093] In some specific embodiments, the content of the monomer is 70%-97%, preferably 85%-97%, more preferably 90%-95%, such as 90%, 91%, 92%, 92.8793%, 92.88%, 93%, 94% or 95%, etc., based on the total weight of the adhesive composition as 100%. When the content of the monomer is 70%-97%, especially 90%-95%, the adhesive composition can be formed more effectively, so that the adhesive layer has a better adhesion. In some further preferred embodiments, the content of the monomer is about 92.88%, based on the total weight of the adhesive composition as 100%.
[0094] Specifically, the monomers include acrylic acid monomers and / or acrylamide monomers, preferably include one or a combination of two or more of acrylic acid, polyacrylamide, polyacrylic acid, and polyhydroxyethyl methacrylate, and more preferably include acrylic acid and / or polyacrylic acid.
[0095] In the present disclosure, a photoinitiator refers to a compound that decomposes and generates free radical species, cationic species, or anionic species by irradiation with active energy rays such as ultraviolet rays or visible light. The present disclosure uses a photoinitiator to enable the adhesive composition of the present disclosure to be cured under ultraviolet light conditions.
[0096] Based on the total weight of the adhesive composition as 100%, the content of the photoinitiator is 0.2%-5%, preferably 0.2%-2%, more preferably 0.3%-1%, such as 0.3%, 0.4%, 0.5%, 0.6%, 0.6192%, 0.62%, 0.7%, 0.8%, 0.9% or 1%, etc. When the content of the photoinitiator is 0.2%-5%, especially 0.3%-1%, the polymerization reaction can be more effectively initiated to obtain an adhesive layer. In some more preferred embodiments, based on the total weight of the adhesive composition as 100%, the content of the photoinitiator is about 0.62%.
[0097] The photoinitiator includes a ketone photoinitiator, preferably including one or a combination of two or more of α-ketoglutaric acid, 2,2-dimethoxy-2-phenylacetophenone, α-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and 2-hydroxy-2-methyl-1-phenyl-1-propanone, more preferably α-ketoglutaric acid.
[0098] Furthermore, the purpose of using a crosslinking agent in the present disclosure is to enable the polymer (e.g., polyacrylic acid compound) obtained by polymerizing monomers (e.g., acrylic acid monomers) to crosslink to form a water-insoluble adhesive layer. If the crosslinking agent is not contained, since the polyacrylic acid compound is also a water-soluble polymer, it will be dissolved by water when in contact with wet tissue, resulting in loss of adhesiveness.
[0099] In order to effectively exert the effect of the crosslinking agent, the content of the crosslinking agent is 1%-10%, preferably 1%-7%, more preferably 1.5%-5%, such as 1.5%, 2%, 2.5%, 3%, 3.096%, 3.1%, 3.5%, 4% or 5%, etc., based on the total weight of the adhesive composition as 100%. When the content of the crosslinking agent is 1%-10%, especially 1.5%-5%, the required adhesive layer can be formed more effectively. In some further preferred embodiments, based on the total weight of the adhesive composition as 100%, the content of the crosslinking agent is about 3.1%.
[0100] Specifically, in the present disclosure, the cross-linking agent includes one or a combination of two or more of methacrylated gelatin, methacrylated hyaluronic acid, polycaprolactone diacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and N,N-methylenebisacrylamide, and more preferably methacrylated gelatin.
[0101] In dura mater repair, the adhesive composition can effectively seal the wound and prevent cerebrospinal fluid leakage, and at the same time, due to its good biocompatibility, it can reduce inflammatory response.
[0102] In the present disclosure, the adhesive composition further comprises an antibiotic compound and / or active metal ions.
[0103] In the present disclosure, active metal ions and antibiotic compounds are integrated into the adhesive layer and attached to the substrate, which improves the antibacterial effect of the biological patch and accelerates tissue vascularization and wound healing, and also has anti-inflammatory properties. The antibiotic compounds and active metal ions not only do not affect the tissue adhesion of the biological patch, that is, they still have excellent bursting strength and strong tissue adhesion, and work together with the substrate and other components of the adhesive composition, so that the biological patch has a continuous drug release ability, can effectively eliminate antibacterial, anti-inflammatory and promote angiogenesis.
[0104] Active metal ions
[0105] In the present disclosure, active metal ions are integrated into the adhesive layer, which not only does not affect the tissue adhesion of the biological patch, but also acts alone or in combination with other components such as antibiotic compounds to give the biological patch antibacterial properties, pro-angiogenic activity and in vivo antibacterial properties.
[0106] In some embodiments, based on the total weight of the adhesive composition as 100%, the content of the component providing active metal ions is 1%-10%, preferably 1%-7%, more preferably 1.5%-5%, for example 1.5%, 2%, 2.5%, 3%, 3.096%, 3.1%, 3.5%, 4% or 5%. When the component providing active metal ions is in the above content, the efficacy of the prepared biological patch can be more effectively exerted. Specifically, in the biological patch of the present disclosure, if the active metal ion content is too high, side effects are likely to occur, such as adverse effects such as excessive pH and cytotoxicity caused by ion precipitation; if the content of active metal ions is too low, it is difficult to exert a unique biological reaction.
[0107] In the present disclosure, the active metal ions include one or a combination of two or more of magnesium ions, copper ions, calcium ions, manganese ions, zinc ions, chromium ions, cobalt ions, strontium ions, and iron ions. It is understood that the component providing the active metal ions can be the above-mentioned ion-containing compounds, such as salts.
[0108] In some preferred embodiments, the active metal ions include magnesium ions. 2+ ), plays a key role in tissue regeneration, especially in promoting cell proliferation, differentiation and angiogenesis. Magnesium ions not only accelerate tissue vascularization and wound healing, but also have anti-inflammatory properties, making them superior to other metal ions in reducing postoperative inflammation.
[0109] In some specific embodiments, when the active metal ions include magnesium ions, the component providing the active metal ions may be magnesium carbonate (MgCO 3 ).
[0110] Antibiotic compounds
[0111] In some embodiments, the antibiotic compound includes one or a combination of two or more of penicillins, cephalosporins, erythromycin, lincomycin, clindamycin, and vancomycin.
[0112] In some preferred embodiments, the antibiotic compound contains vancomycin to further enhance the antibacterial effect of the biological patch. Vancomycin (Van), a potent antibacterial agent, can effectively inhibit bacterial growth and reduce the risk of postoperative infection.
[0113] In some embodiments, based on the total weight of the adhesive composition as 100%, the content of the antibiotic compound is 0.1%-3%, preferably 0.1%-1%, more preferably 0.15%-0.5%, for example 0.15%, 0.20%, 0.25%, 0.03%, 0.396%, 0.31%, 0.35%, 0.4% or 0.5%.
[0114] When antibiotic compounds and / or active metal ions are used, the asymmetric adhesive biological patch of the present invention is applied to dura mater injury, and the asymmetric adhesive biological patch can seal cerebrospinal fluid leakage, release vancomycin and / or magnesium ions (Mg 2+ ), promoting tissue regeneration, has great potential in the clinical application of dura mater repair and provides a new option for improving the clinical effect of dura mater repair.
[0115] In some specific embodiments, the present disclosure designs an asymmetric adhesive repair biological patch based on SIS, by using PAA hydrogel and magnesium ions (Mg 2+ ) give it antibacterial and pro-angiogenic properties. PAA hydrogels are widely used in wound dressings and tissue engineering scaffolds due to their strong adhesion and biocompatibility. In dura mater repair, PAA can effectively seal wounds and prevent CSF leakage, while reducing inflammatory responses due to its good biocompatibility.
[0116] By combining biocompatible SIS, adhesive PAA, vancomycin and pro-angiogenic magnesium ions, the present invention develops a multifunctional dura mater repair biological patch, which provides a new option for improving the clinical effect of dura mater repair.
[0117] In vitro experiments showed that the SIS / PAA / Van@Mg biopatch has excellent bursting strength, strong tissue adhesion and sustained drug release, and can effectively eliminate Staphylococcus aureus (S.aureus) and promote angiogenesis. In the dura mater injury models of rats, rabbits and beagles, the SIS / PAA / Van@Mg biopatch demonstrated superior antibacterial properties, effective CSF sealing effect and enhanced tissue regeneration ability. The results show that the SIS / PAA / Van@Mg biopatch has great potential in the clinical application of dura mater repair.
[0118] <Second Aspect>
[0119] The second aspect of the present disclosure provides a method for preparing the asymmetric adhesive biological patch according to the first aspect of the present disclosure, which comprises the steps of mixing the components of the adhesive layer and then compounding with the substrate. The method for preparing the asymmetric adhesive biological patch disclosed in the present disclosure is simple and easy to implement, and the raw materials are easy to obtain, and it is suitable for mass production.
[0120] In some specific embodiments, the preparation method comprises the following steps:
[0121] a step of obtaining an adhesive composition;
[0122] The adhesive composition is present on at least one surface of the substrate, and an asymmetric adhesive biological patch is obtained after chemical reaction.
[0123] Preferably, in the present disclosure, the adhesive composition is dissolved in a solvent to form a pre-polymerization solution, and the pre-polymerization solution is made to exist on at least one surface of the substrate.
[0124] Furthermore, the present disclosure does not specifically limit the solvent, and it can be an inorganic solvent commonly used in the art. In order to better form a gel and thus obtain the desired adhesive layer, the solvent described in the present disclosure is deionized water.
[0125] In some embodiments, based on the total weight of the prepolymer solution as 100%, the content of the monomer is 10%-50%, preferably 20%-40%, more preferably 25%-35%, for example 25%, 27%, 28%, 30%, 31%, 33%, 35%, etc.
[0126] In some embodiments, based on the total weight of the pre-polymerization solution as 100%, the content of the photoinitiator is 0.05%-0.5%, preferably 0.1%-0.5%, for example 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.32%, 0.35%, 0.38%, 0.4%, 0.42%, 0.45%, 0.48%, etc.
[0127] In some embodiments, based on the total weight of the pre-polymer solution as 100%, the content of the cross-linking agent is 0.1%-5%, preferably 0.3%-5%, more preferably 0.5%-5%, for example 0.5, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, etc.
[0128] In some embodiments, based on the total weight of the prepolymer solution as 100%, the content of the component providing active metal ions is 0.1%-5%, preferably 0.5%-2%, more preferably 0.8-1.5%, for example 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%.
[0129] In some embodiments, based on the total weight of the prepolymer solution as 100%, the content of the antibiotic compound is 0.01%-1%, preferably 0.05%-0.3%, for example, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%.
[0130] Finally, the adhesive composition is made to exist on at least one surface of the substrate, and an asymmetric adhesive biological patch is obtained after chemical reaction. Specifically, the mixed product can be made to exist on at least one surface of the substrate by one or a combination of two or more of paving, coating, casting and spraying.
[0131] In some specific embodiments, the conditions of the chemical reaction include being carried out under the irradiation of ultraviolet light, and the chemical reaction may include polymerization reaction and photocrosslinking reaction; through the chemical reaction, the monomers in the adhesive composition can produce a polymerization reaction, thereby improving the mechanical properties and tissue adhesion of the asymmetric adhesive biological patch.
[0132] Preferably, the power of the ultraviolet light is 200-400W, for example: 220W, 250W, 280W, 300W, 320W, 350W, 380W, etc.; the irradiation time is 25-40 minutes, for example: 25 minutes, 27 minutes, 30 minutes, 32 minutes, 35 minutes, 40 minutes, etc. When the power of the ultraviolet light is 200-400W and the irradiation time is 25-40 minutes, both the polymerization reaction and the photocrosslinking reaction can be effectively carried out.
[0133] In addition, in the present disclosure, every 1 cm 2 The amount of the prepolymer solution in the adhesive layer used can be 10-100 μL, preferably 20-80 μL, more preferably 40-60 μL, such as 40 μL, 45 μL, 50 μL, 55 μL, 60 μL. When the above amount is used, the asymmetric adhesive biological patch disclosed in the present invention has better bursting strength and tissue adhesion, and has better sustained drug release ability, antibacterial performance, effective cerebrospinal fluid sealing effect and enhanced tissue regeneration ability.
[0134] <Third Aspect>
[0135] The third aspect of the present disclosure provides a use of the asymmetric adhesive biological patch according to the first aspect of the present disclosure for preparing tissue repair products, in particular, for preparing dura mater repair materials, skull repair materials, and postoperative defect repair materials.
[0136] In some embodiments, there is provided a use of the asymmetric adhesive biological patch described in the first aspect of the present disclosure in preparing a product for tissue repair; specifically, the product for tissue repair includes a dura mater repair material, a skull repair material, or a postoperative defect repair material.
[0137] In some embodiments, the asymmetric adhesive biological patch described in the first aspect of the present disclosure is provided, which is used for tissue repair; specifically, the tissue repair includes dura mater repair, skull repair, or post-operative defect repair.
[0138] In some embodiments, a tissue repair method is provided, which includes the step of using the asymmetric adhesive biological patch described in the first aspect of the present disclosure; specifically, the tissue repair includes dura mater repair, skull repair or post-operative defect repair.
[0139] Example
[0140] The embodiments of the present disclosure will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0141] Materials and Methods
[0142] 1. Materials
[0143] Acrylic acid, vancomycin and magnesium carbonate (MgCO3) were purchased from Aladdin (China), α-ketoglutaric acid was purchased from Sigma-Aldrich (USA), methacrylated gelatin (Gel-MA) was purchased from Sigma, and porcine SIS was provided by Beijing Bohui Ruijin Biotechnology Co., Ltd. (China). Unless otherwise specified, other chemical reagents were of chemical grade and provided by Beijing Chemical Reagent Co., Ltd. (China). L929 cells and HUVECs were obtained from Wuhan Punosai Life Science Co., Ltd.
[0144] 2. Preparation of asymmetric adhesive biological patches
[0145] Based on the total weight of the prepolymer solution as 100%, acrylic acid (30.0 wt.%), Gel-MA (1.0 wt.%) and α-ketoglutaric acid (0.2 wt.%) were dissolved in deionized water (i.e., acrylic acid prepolymer solution, or simply prepolymer solution) and heated at 50 μL cm -2The ratio of 1:1 was coated on SIS. After irradiation with 300W ultraviolet light for 30 minutes, the water in the prepolymerization solution was completely evaporated to prepare a SIS / PAA biological patch. Similarly, based on the total weight of the prepolymerization solution as 100%, by further adding vancomycin (0.1wt.%), MgCO3 (1.0wt.%), vancomycin (0.1wt.%) and MgCO3 (1.0wt.%) into the prepolymerization solution, and then irradiating with 300W ultraviolet light for 30 minutes, the water in the prepolymerization solution was completely evaporated to prepare SIS / PAA / Van, SIS / PAA@Mg and SIS / PAA / Van@Mg asymmetric adhesive biological patches respectively, and the adhesive layer of the above biological patches does not contain water and is in a dry state.
[0146] 3. Characterization of Asymmetric Adhesive Biopatch
[0147] The biopatch was quenched in liquid nitrogen and the fracture surface was observed using a scanning electron microscope (SEM, S4800, Hitachi, Japan) after platinum sputtering. Element distribution analysis was performed using energy dispersive spectroscopy (EDS). Fourier transform infrared spectra (FT-IR) were recorded using an ATR-FT-IR spectrometer (Thermo Nicolet iS5, Thermo Fisher Scientific, USA).
[0148] 4. Drug release from asymmetric adhesive biopatch
[0149] The standard shape of SIS / PAA / Van@Mg biopatch (2 cm×2 cm) was placed in a centrifuge tube, 5 mL of PBS solution was added, and the centrifuge tube was then placed in a shaking water bath at 37°C and 50 rpm. The supernatant was taken out on the 1st, 4th and 7th day, and its absorbance was measured at 280 nm using a UV-visible spectrophotometer. The vancomycin concentration was calculated based on the vancomycin standard curve.
[0150] Similarly, Mg 2+ The release experiment was carried out according to the above method, the only difference was that the sampling time was 1 day, 4 day, 7 day, 14 day and 21 day. The collected supernatant was sent to an inductively coupled plasma spectrometer (ICP-OES, Shimadzu ICPE-9800, Japan) to detect Mg 2+ concentration.
[0151] 5. Tissue Adhesion of Asymmetric Adhesive Biopatch
[0152] The bursting strength test was performed according to ASTM F2392. A 5 mm defect was created in a 3 cm section of porcine colon using a biopsy puncture. A biopatch (2 cm × 2 cm) was placed on the defect and adhered at room temperature for 60 minutes. The biopatch was pumped at 2 mL min -1 Pressure is applied at a rate of 100° until leakage occurs, at which point the bursting strength is recorded.
[0153] Shear bond strength test was performed according to ASTM F2255 standard. The pig skin was cut into pieces of 4 cm × 2.5 cm, and then the biopatch was applied to one of the pieces of pig skin, covering an area of 2 cm × 2 cm. The two pieces of skin were bonded together in opposite directions at room temperature. After 60 minutes, the shear bond strength was measured using a universal testing machine at 5 mm min -1 The force-displacement curve in the shear direction was measured at a rate of 1000 rpm and the maximum shear force (F max ). The calculation formula of shear bond strength (Pa) is:
[0154]
[0155] The interfacial toughness test was performed according to ASTM F2256. The pig skin was cut into pieces of 4 cm × 2.5 cm, and then the biopatch was applied to one of the pieces of pig skin, covering an area of 2.5 cm × 1 cm. The two pieces of skin were aligned and bonded together at room temperature. After 60 minutes, the universal testing machine was used to test the toughness of the skin at 5 mm min. -1 The force-displacement curve in the shear direction was measured at a rate of 1.5 % and the maximum peeling force (F max ). The calculation formula of interface toughness (Jm-2) is:
[0156]
[0157] 6. Cytocompatibility of asymmetric adhesive biopatch
[0158] (1) Hemolysis test
[0159] According to the ISO10993 standard, a 2cm×3cm biological patch was placed in a 2mL centrifuge tube containing 1mL PBS and incubated at 37°C for 30 minutes to obtain an extract. After incubation, 900μL of the extract was mixed with 200μL of whole rabbit blood as the experimental group. In the control group, 900μL PBS was mixed with 200μL whole rabbit blood as a negative control, while 900μL Triton X-100 was mixed with 200μL whole rabbit blood as a positive control. All samples were incubated together at 37°C for 1 hour. Then, centrifuged at 4000rpm for one minute using a desktop high-speed centrifuge. Take a picture, transfer 100μL of the supernatant to a 96-well plate, and measure the absorbance at 545nm using an enzyme reader. The formula for calculating the hemolysis rate (%) is:
[0160]
[0161] A M , A N and A P Represent the absorbance values of the experimental group, negative control group and positive control group, respectively.
[0162] (2) Compatibility test of L929 fibroblasts
[0163] According to the ISO10993 biological testing standard, the SIS-based biological patch was immersed in the cell culture medium at a scale of 6 cm 2 mL -1 . After 24 hours, the extract was obtained and used to co-culture L929 fibroblasts (1,000 cells per well) in 48-well plates. The co-culture was maintained for 24 hours. Cell viability was assessed using CCK-8 reagent, and the absorbance was measured at 450 nm by a microplate reader (Bio-Rad 680, USA). In addition, live-dead cell imaging was performed using a laser confocal microscope (CLSM, TCS SP8, Leica, Germany) after staining with Calcein-AM / PI fluorescent dye (Aladdin, China).
[0164] 7. Antibacterial Experiment of Asymmetric Adhesive Biopatch
[0165] (1) Morphology observation
[0166] A 2 cm × 3 cm biological patch was placed in a 60 mm diameter culture dish containing 50 μL of bacterial suspension (1 × 10 5 CFU mL -1) and 10 mL TSB medium. The culture dish was incubated at 37°C for 24 hours. After incubation, the medium was removed and the biopatch was rinsed three times with deionized water. The biopatch was then fixed in a 2.5% glutaraldehyde solution for 12 hours. After fixation, the glutaraldehyde solution was discarded, and the biopatch was rinsed twice with 75% ethanol and sent for SEM observation after complete drying.
[0167] (2) Inhibition zone
[0168] The biopatch was cut into a disk with a diameter of 1 cm. 100 μL of S. aureus suspension (1×10 5 CFU mL -1 ) and spread evenly using a sterile spreading stick. Each biopatch disc is then placed in a specific area of the agar plate. The plates are placed in a temperature and humidity controlled incubator at 37°C for 24 hours. After the incubation is complete, take a photo of the plate for analysis.
[0169] (3) Bacterial activity
[0170] A 2 cm × 2 cm sample was placed in a 60 mm diameter Petri dish containing 50 μL of 1 × 10 5 CFU mL -1 of bacterial suspension and 10mL of TSB medium. The culture dish was then incubated at 37°C for 24 hours. After the incubation, 100μL of the solution was transferred to a 96-well plate and its absorbance was measured at 600nm. In addition, 1mL of the solution was transferred to a 1.5mL EP tube and photographed using a camera. The calculation formula for the antibacterial rate (%) is:
[0171]
[0172] A C represents the absorbance value of the control group (the sample of the control group is the absorbance value containing only the initial inoculated bacteria), A M Represents the absorbance value of the experimental group.
[0173] (4) Biofilm formation
[0174] A 2 cm × 2 cm sample was placed in a 60 mm diameter Petri dish containing 50 μL of 1 × 10 5 CFU mL -1of bacterial suspension and 10mL of TSB medium. The culture dish was then incubated at 37°C with shaking at 50rpm for 24 hours. After the incubation, the sample was removed and placed in a 24-well plate, and 120μL of 0.1% crystal violet solution (dissolved in methanol) was added to each well to stain the biofilm. The plate was left at room temperature for 10 minutes, and then the crystal violet solution was removed. The wells were washed three times with PBS and air dried. Subsequently, 200μL of 95% ethanol was added to each well to elute the crystal violet dye from the biofilm. The plate was left at room temperature for 15 minutes, and then a camera was used to take a picture. Finally, 100μL of the eluted solution was transferred to a 96-well plate, and the absorbance was measured at 540nm to assess biofilm formation. The calculation formula for biofilm biomass (%) is:
[0175]
[0176] A C represents the absorbance value of the control group (the sample of the control group is the absorbance value containing only the initial inoculated bacteria), A M Represents the absorbance value of the experimental group.
[0177] 8. Vascularization activity of asymmetric adhesive biopatch
[0178] (1) VEGF immunofluorescence staining
[0179] To evaluate the angiogenic potential of the extract, HUVECs were used as study cells. 5000 HUVECs were seeded in 48-well plates and co-cultured with the biopatch extract for 7 days, with the culture medium changed every other day. After the culture, the cells were stained with the primary VEGF antibody (ab32152, Abcam, UK), FITC-labeled F-actin, and fluorescent secondary antibodies. After incubation in the dark for 30 minutes, CLSM was used to observe the expression of VEGF in the cells. Subsequently, the fluorescence intensity was semi-quantitatively analyzed using Image Pro Plus software.
[0180] (2) Tube Formation Experiment
[0181] Matrigel (Corning, USA) was used to create the matrix of the cell culture plate. 5000 HUVECs were seeded on the Matrigel and co-cultured with the biopatch extract for 12 hours. Subsequently, the tube formation was observed under an optical microscope. The spacing between the tubular networks was semi-quantitatively measured using ImageJ software.
[0182] (3) Scratch test
[0183] 5000 HUVECs were seeded into 24-well plates. When the cells reached about 80% confluence, a sagittal scratch with a width of 200 μm was created using a pipette tip. Then, the cells were co-cultured with the biological patch extract. After 24 hours, cell migration was observed under a microscope. The trace distance of cell migration was semi-quantitatively analyzed using ImageJ software.
[0184] 9. In vivo dura mater repair experiment
[0185] All animal experiments were in accordance with the Tianjin Medical Laboratory Animal Guidelines, and the animal experimental protocols were approved by the Institutional Animal Care and Use Committee of Yishengyuan Gene Technology (Tianjin) Co., Ltd. (ethical approval numbers YSY-DWLL-2024433, 2024434, 2024435). (1) Infection rat dura mater injury model
[0186] After the mice were anesthetized, a 5 mm circular defect was created in the skull using a trephine drill and the excised bone was removed. A scalpel was then used to cut the dura mater at the base of the skull in a straight line. The mice were randomly divided into four groups: 1) Control group, in which S. aureus (10 5 CFU) without other treatment. 2) Introducing S. aureus (10 5 CFU) and then implanted the SIS biological patch. 3) Introduced S. aureus (10 5 CFU) and then implanted SIS / PAA / Van biopatch. 4) Introduced S. aureus (10 5 CFU) were implanted with SIS / PAA / Van@Mg biopatch. The wound was then sutured in layers.
[0187] At 1 and 4 weeks after surgery, the mice were sacrificed and tissues from the dura mater injury site were collected for histological and immunofluorescence analysis, including H&E, TNF-α (ab220210, Abcam, UK), CD163 (ab182422, Abcam, UK), and DAPI staining. 3 Granulation tissue was placed in 1 mL of sterile saline for two hours, and then 50 μL of the supernatant was spread on a sterile agar plate. The plate was incubated at 37°C for 24 hours to assess the formation of bacterial colonies. Dura mater tissue collected after 1 week was stained with Giemsa to identify any residual exogenous bacteria. Fluorescence intensity was semi-quantitatively analyzed using Image ProPlus software. (2) New Zealand White Rabbit Dura Mater Injury Model
[0188] After anesthesia, New Zealand rabbits underwent surgery to create a 10 mm circular skull defect using a trepanation drill, and the excised bone fragment was removed. Then, a scalpel was used to make a straight line incision along the dura mater below the skull. The rabbits were randomly divided into three groups: 1) control group, suture only. 2) SIS implanted after suture. 3) SIS / PAA / Van@Mg implanted after suture. The wound was then sutured in layers.
[0189] At 2 and 4 weeks after surgery, rabbits were sacrificed and tissues from the dura mater injury site were collected. These tissues were fixed in 4% paraformaldehyde for 24 hours and then sectioned for histological and immunofluorescence analysis, including H&E, Masson's trichrome staining, TNF-α (7124-MSM1-P1BX, ThermoFisher, USA), TGF-β (MA1-21595, ThermoFisher, USA) and VEGF (MA5-13182, ThermoFisher, USA). Collagen formation and fluorescence intensity were semi-quantitatively evaluated using Image Pro Plus software. At 4 weeks after surgery, blood samples were collected for hematological analysis. In addition, heart, liver, spleen, lung, and kidney tissues were examined by pathological staining.
[0190] (3) Beagle dog dura mater injury model
[0191] Under anesthesia, beagle dogs underwent craniotomy, and a 20 mm circular skull defect was created using a trephine drill, and the excised bone fragments were discarded. Then, a scalpel was used to make a straight line incision along the dura mater below the skull. The dogs were randomly divided into three groups: 1) control group, suture only. 2) SIS implanted after suture. 3) SIS / PAA / Van@Mg implanted after suture. The wound was then sutured in layers. Electrocardiogram (ECG) monitoring was performed before surgery, 4 weeks, and 8 weeks after surgery for the SIS / PAA / Van@Mg group. At 8 weeks after surgery, the dogs were sacrificed, and tissues from the dura mater injury site were collected for histological and immunofluorescence analysis, including Masson's trichrome staining, VEGF (MA1-16629, ThermoFisher, USA), collagen (ab24137, Abcam, UK), TLR2 (ab9100, Abcam, UK), CD4 (MA5-28357, ThermoFisher, USA), and DAPI. Collagen expression was analyzed by collagen fluorescence staining, and vascularization level was analyzed by VEGF fluorescence staining, both of which were semi-quantitatively analyzed using Image Pro Plus software. At 8 weeks after surgery, heart, liver, spleen, lung, and kidney tissues were also collected for pathological staining.
[0192] 10. Statistical Analysis
[0193] All data were expressed as mean ± standard deviation (SD). GraphPad 9.4 software was used for one-way analysis of variance (ANOVA) statistical analysis. * P<0.05, ** P<0.01, *** The differences between the groups with P < 0.001 were considered statistically significant.
[0194] Example 1 Preparation and Characterization of Asymmetric Adhesive Biopatch
[0195] The present invention discloses an asymmetric adhesive biopatch using α-ketoglutaric acid as a photoinitiator, which is a metabolite from the human tricarboxylic acid cycle. Vancomycin and magnesium carbonate are dissolved and suspended in a prepolymer solution, and Gel-MA is used as a crosslinker. The prepolymer solution is coated on the SIS biopatch and irradiated under ultraviolet light for 30 minutes (300W) to induce free radical polymerization and crosslinking, thereby forming a SIS / PAA / Van@Mg biopatch ( Figure 1 The prepared SIS / PAA / Van@Mg biopatch exhibits excellent flexibility, making it suitable for various drug delivery devices and enhancing its applicability in endoscopic surgery ( Figure 1 b). FT-IR shows that the SIS / PAA / Van biopatch has a peak at 1585 cm -1 There is a characteristic peak at , which corresponds to the C=C stretching vibration of the aromatic ring in vancomycin ( Figure 1 c in Figure 1). This peak confirms that vancomycin is successfully incorporated into the PAA gel coating. SEM images show that the PAA coating is evenly coated on the SIS matrix, and elemental scanning confirms the uniform distribution of magnesium ( Figure 1 d). The drug release behavior was evaluated by soaking the patches in PBS. Vancomycin and Mg 2+ The release was sustained over 7 days, with initial concentrations on the first day being 30.57±5.72ppm ( Figure 2 a) and 228.22±50.08ppm( Figure 2 b) It has been reported that vancomycin and Mg 2+ The SIS / PAA / Van@Mg dura mater repair biopatch has a good potential and can achieve effective therapeutic effects.
[0196] Example 2 Tissue Adhesion of Asymmetric Adhesive Biological Patch
[0197] The tissue adhesion properties of the SIS / PAA / Van@Mg dura mater repair biopatch were evaluated according to the ASTM standards for tissue adhesives (ASTM F2392, ASTM F2255, and ASTM F2256). The tissue adhesion of the SIS material was poor, and the bursting strength could not be measured. The shear bond strength was 2.58±1.26 kPa, and the interface toughness was 8.85±3.13 J m -2 , which is insufficient for sealing CSF leaks because intracranial pressure can reach 1.96 kPa. The tissue adhesion of SIS / PAA dura mater repair materials was significantly improved by coating with PAA adhesive. For example, the bursting strength of SIS / PAA was 26.43 ± 1.52 kPa, the shear bond strength was 25.70 ± 1.41 kPa, and the interface toughness was 118.90 ± 10.40 Jm -2 The addition of vancomycin and magnesium carbonate did not affect these adhesion properties ( Figure 3 The bursting strength of SIS / PAA / Van@Mg was still sufficient to seal CSF leaks and was measured to be 20.50±2.89 kPa. In addition, the asymmetric adhesive biopatch exhibited strong adhesion properties in a variety of tissues including heart, liver, spleen, and lung ( Figure 3 Compared to recent advances in tissue adhesives for neurosurgical applications, particularly in dura mater and spinal dura mater sealing to prevent CSF leakage, the above experimental data indicate that the SIS / PAA / Van@Mg biopatch of the present disclosure provides superior bursting strength and tissue adhesion strength, confirming its leading position in the latest developments in this field ( Figure 3 e) in.
[0198] Example 3 Cytocompatibility of asymmetric adhesive biopatch
[0199] In order to evaluate the cell compatibility of the biological patch, the present embodiment conducted a hemolysis test by co-culturing the biological patch extract with red blood cells, and used L929 fibroblasts for cell activity detection. The hemolysis rate of all SIS-based biological patches was less than 5% ( Figure 4 a), which complies with biomedical safety standards. CCK-8 assay and live / dead staining of L929 cells showed no significant difference in cell activity between the SIS-based biological patch and the control group, and no significant difference between the materials ( Figure 4 In addition, fluorescent staining showed good spreading of spindle-shaped cells ( Figure 4 c) in the figure further confirmed the excellent cell compatibility of the biological patch.
[0200] Example 4 Antibacterial properties of asymmetric adhesive biological patches
[0201] To evaluate the antibacterial properties of the developed biopatch, S. aureus was selected because vancomycin is effective against Gram-positive bacteria and S. aureus is often associated with intracranial infections. The antibacterial experiment was performed by co-culturing the biopatch with bacteria, followed by plate culture, OD 600 Measurements and crystal violet experiments were performed to comprehensively evaluate the antibacterial effect. SEM images showed that the antibacterial activity of the SIS biopatch was minimal, and a large amount of S. aureus was attached to the surface of the material. In contrast, the S. aureus on the SIS / PAA surface showed slight deformation, which may be due to the electrostatic interaction between the anionic carboxyl groups in the PAA coating and the bacterial biofilm. More obvious bacterial deformation was observed in the SIS / PAA / Van, SIS / PAA@Mg, and SIS / PAA / Van@Mg groups, which may be attributed to the inhibitory effects of vancomycin on biofilm formation and bacterial RNA synthesis, as well as the Mg 2+ Bactericidal effect through osmotic lysis. Among these groups, the SIS / PAA / Van@Mg group showed the most significant bacterial damage ( Figure 5 In the inhibition zone experiment, the SIS / PAA / Van@Mg group also showed the largest inhibition zone ( Figure 5 b) OD of the co-culture medium 600 The values measured further highlighted the antibacterial effect of the biopatch, with the bacterial inhibition rates of SIS being 1.28±0.80%, SIS / PAA being 10.90±0.40%, SIS / PAA@Mg being 99.49±0.11%, SIS / PAA / Van being 52.18±0.48%, and SIS / PAA / Van@Mg being 99.17±0.11% ( Figure 5 c). These results highlight the strong potential of SIS / PAA / Van@Mg for in vivo antimicrobial applications. In addition, the inhibition of biofilm formation was evaluated using the crystal violet assay ( Figure 5 The biofilm biomass was 100.00±6.65% in the SIS group, 100.98±6.51% in the SIS / PAA group, 49.44±2.87% in the SIS / PAA / Van group, and 39.31±2.18% in the SIS / PAA / Van@Mg group ( Figure 5 e). These findings confirm the successful development of a dura mater repair material with strong antimicrobial properties.
[0202] Example 5 Angiogenic activity of asymmetric adhesive biological patch
[0203] Considering Mg 2+In order to evaluate the potential of the biopatch to stimulate vascularization, the present invention prepared extracts of the biopatch according to the ISO10993 guidelines and evaluated their effects on HUVECs. In order to evaluate the ability of the biopatch to promote vascularization, the present invention performed a cell scratch test, a tube formation test, and immunofluorescence staining. In the scratch test, a uniform scratch with a width of 200 μm was created using a pipette tip ( Figure 6 (a) After 24 h of co-culture with the extract, no significant cell migration was observed in the control, SIS, SIS / PAA, and SIS / PAA / Van groups. Quantitative analysis showed that the scratch healing distances were 109.11±5.90μm, 96.74±19.16μm, and 90.54±5.73μm, respectively. In contrast, SIS / PAA@Mg and SIS / PAA / Van@Mg showed significant cell migration, with scratch healing distances of 35.44±5.90μm and 25.89±8.90μm, respectively. Figure 6 d). In the tube formation experiment, the tube formation of SIS / PAA@Mg and SIS / PAA / Van@Mg was significantly increased compared with other groups ( Figure 6 (b) The microtubule length of the SIS / PAA / Van@Mg group reached 474.84±95.54μm, which was 3.34 times and 2.11 times that of the control group and SIS group ( Figure 6 e). Immunofluorescence staining of VEGF further confirmed that the fluorescence intensity of the SIS / PAA@Mg and SIS / PAA / Van@Mg groups was significantly higher, 3.27 times and 3.47 times that of the control group, respectively ( Figure 6 c and Figure 6 f)). Interestingly, VEGF expression in the SIS group also showed some upregulation compared with the control group, which may be due to the promotion of vascular differentiation by residual TGF-β and FGF factors in SIS. These results verify that the SIS / PAA / Van@Mg biopatch has significant antibacterial properties and enhanced vascularization, highlighting its potential for effective application in dura mater repair.
[0204] Example 6 In vivo antibacterial activity of asymmetric adhesive biological patches
[0205] In order to further verify the in vivo antibacterial effect of the biological patch, this example conducted a study using a rat dura mater injury model to evaluate the repair effect of the biological patch under exogenous S. aureus challenge. In this model, the rat was anesthetized and a circular defect with a diameter of 5 mm was established on the skull. Then, the dura mater was carefully dissected, and S. aureus and different biological patches were implanted into the dura mater defect, followed by suturing ( Figure 7 One week after surgery, the rats were killed and the granulation tissue (1 mm3 ) and soaked in sterile saline for two hours. The tissue was then placed on a sterile agar plate and incubated at 37°C for 24 hours. Figure 7 As shown in (b), a large number of colonies were observed in the control group and the SIS group, while the colonies in the SIS / PAA / Van group were significantly reduced, and the colonies in the SIS / PAA / Van@Mg group were the least, indicating that vancomycin and Mg were released simultaneously. 2+ Effectively enhanced the antibacterial activity. One week after surgery, histological analysis of H&E staining showed obvious tissue necrosis in the control group, mainly due to bacterial exotoxins. Giemsa staining further confirmed the residual S. aureus in the control and SIS groups. In contrast, no obvious inflammatory response or bacterial residues were observed in the SIS / PAA / Van and SIS / PAA / Van@Mg groups. The inflammatory marker TNF-α decreased to 0.21 times that of the control group, while the anti-inflammatory marker CD163 increased to 4.78 times that of the control group. Four weeks after surgery, the control and SIS groups formed dense fibrous tissue due to bacterial influence, while the SIS / PAA / Van and SIS / PAA / Van@Mg groups showed normal cell infiltration into the biological patch. It is worth noting that the CD163 expression in the SIS / PAA / Van@Mg group was 8.60 times higher than that in the control group and 7.54 times higher than that in the SIS group ( Figure 7 c and Figure 7 d) in the figure). These results indicate that the implanted biopatch has excellent biocompatibility and outstanding antibacterial effect in vivo, highlighting its potential for effective dura mater repair applications.
[0206] Example 7 Asymmetric Adhesive Biological Patch Repair of Rabbit Dura
[0207] To evaluate the tissue repair capabilities of the asymmetric adhesive biopatch, a New Zealand rabbit model was used in this example. A 10 mm skull defect was created during craniotomy, resulting in dura mater injury. The defect was repaired by a suturing procedure (approximately 2-3 stitches), followed by implantation of the SIS-based dura mater repair biopatch. Autologous bone graft was then placed in the defect, and the wound was sutured ( Figure 8 A). Histological evaluation 2 weeks after surgery showed no significant inflammation in either SIS or SIS / PAA / Van@Mg implants using H&E staining and Masson's trichrome staining ( Figure 8 b). Four weeks after surgery, the implanted biological patch began to gradually degrade, and the surrounding dura mater tissue showed a large amount of collagen formation ( Figure 8c). Quantitative analysis showed that collagen deposition in the SIS / PAA / Van@Mg group reached 35.33±9.29% at 2 weeks after surgery and 57.67±9.61% at 4 weeks. In contrast, the values of collagen formation in the control group and SIS group at 4 weeks were 14.33±3.06% and 31.67±4.16%, respectively ( Figure 8 VEGF fluorescence staining showed that SIS / PAA / Van@Mg implants significantly increased vascularization 2 weeks after surgery ( Figure 8 e), VEGF expression was 6.08 times that of the control group. This increased VEGF expression was still maintained 4 weeks after surgery, still 4.08 times that of the control group ( Figure 8 f) in.
[0208] This example also evaluated the repair process of the dura mater by focusing on specific markers related to tissue repair, including TNF-α and TGF-β. Two weeks after surgery, the TNF-α level in the SIS / PAA / Van@Mg group was significantly lower, reaching 0.16 times that of the control group, indicating a decrease in inflammation ( Fig. 9 In addition, the expression of TGF-β in the SIS / PAA / Van@Mg group was 3.64 times that in the control group ( Fig. 9 b). Four weeks after surgery, the TGF-β level in the SIS / PAA / Van@Mg group remained elevated, reaching 2.31 times that of the control group and 1.38 times that of the SIS group ( Fig. 9 c) in.
[0209] To further confirm the biocompatibility and safety of the biopatch, this example conducted a comprehensive examination of the heart, liver, spleen, lungs, and kidneys, as well as a hematological evaluation, 4 weeks after implantation. Histological analysis showed that the SIS / PAA / Van@Mg implant did not cause any significant adverse reactions. The histological appearance of the organs in the SIS / PAA / Van@Mg group was comparable to that in the control group, with no abnormalities ( Fig.10 In addition, the present embodiment measured blood routine and serum biochemical parameters such as white blood cells (WBC), red blood cells (RBC), alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The results showed that there was no significant difference between the SIS / PAA / Van@Mg group and the control group ( Fig.11 a and b), indicating that the SIS / PAA / Van@Mg implants did not induce any systemic immune or toxic responses. These findings confirm that the SIS / PAA / Van@Mg biopatch has excellent biocompatibility and safety, with no significant effects on vital organ function or blood routine and serum biochemical parameters. Combined with its effective tissue regeneration effect, these biopatch demonstrates strong potential for safe and efficient dura mater repair applications.
[0210] Example 8 Asymmetric Adhesive Biological Patch for Repair of Dura Matter in Beagle Dogs
[0211] In order to comprehensively evaluate the clinical efficacy and safety of SIS / PAA / Van@Mg, we consulted medical device registration experts and clinicians. Based on their suggestions, this example modified the research methods to make it closer to clinical operations and conducted a detailed study using beagle dogs. The methods of this study are similar to the experiments disclosed in this disclosure on New Zealand rabbits, but were adjusted to replicate human clinical practice. In this experiment, a skull defect was created on the skull of a beagle dog, and a sagittal incision of approximately 2 cm was made at the base of the dura mater. Following standard clinical procedures, airtight closure of the dura mater was achieved by watertight suture. Subsequently, SIS / PAA / Van@Mg was implanted for secondary sealing, followed by re-implantation of autologous bone, and the wound was sutured ( Fig.12 a in Figure 1). The cardiac safety of SIS / PAA / Van@Mg was monitored at different time points (preoperatively, 4 weeks, and 8 weeks postoperatively), assessed using ECG. Initially, the dogs had a normal heart rate with regular R waves and heart rate within the normal range. Although a minor transient effect on cardiac electrical activity was observed 4 weeks after surgery, cardiac function generally returned to baseline levels by 8 weeks, indicating a favorable safety profile ( Fig.12 (b) After 8 weeks of implantation, the animals were euthanized and the damaged dura mater was histologically stained. Masson's trichrome staining and VEGF / collagen / DAPI immunofluorescence staining showed that the collagen formation in the new dura mater in the SIS / PAA / Van@Mg group was denser and more orderly ( Fig.12 d in the figure). The collagen fibers are well arranged and the surrounding blood vessels are more abundant ( Fig.12 e in the figure). Quantitative analysis showed that the collagen content of the SIS / PAA / Van@Mg group was 75.00±6.00%, while that of the control group was 47.00±7.21%; the vascularization level of the SIS / PAA / Van@Mg group was 2.15 times that of the control group ( Fig.12 c). These findings strongly support the potential of SIS / PAA / Van@Mg as an effective dura mater repair material for clinical applications. The biopatch showed good safety and enhanced efficacy in promoting tissue regeneration and vascularization, making it a promising option for future clinical use.
[0212] In addition, 8 weeks after surgery, the SIS / PAA / Van@Mg biopatch continued to demonstrate excellent biocompatibility and biosafety. Histological evaluation of the dura mater at the implantation site revealed no significant inflammatory or immune rejection reactions ( Fig.13 In addition, pathological staining of major organs (including heart, liver, spleen, lung, and kidney) showed no abnormalities ( Fig.14These findings further confirm that the SIS / PAA / Van@Mg biopatch has no adverse effects on major body systems and enhances its potential for safe clinical application in dura mater repair.
[0213] In the present disclosure, an asymmetric adhesive biopatch for dura mater repair is developed, in which active ingredients (such as vancomycin, MgCO3) are integrated into the PAA adhesive coating and attached to the SIS matrix (i.e., SIS / PAA / Van@Mg) ( Fig.15 a in the figure). In vitro experiments showed that the SIS / PAA / Van@Mg biopatch had excellent bursting strength, strong tissue adhesion and sustained drug release, and could effectively eliminate S. aureus and promote angiogenesis. In the dura mater injury models of rats, rabbits and beagles, the SIS / PAA / Van@Mg biopatch demonstrated superior antibacterial properties, effective CSF sealing effect and enhanced tissue regeneration ability ( Fig.15 b). The results showed that the SIS / PAA / Van@Mg biopatch has great potential in the clinical application of dura mater repair.
[0214] In the present disclosure, an asymmetric adhesive biological patch with targeted drug delivery function was developed for repairing the dura mater. By integrating vancomycin (Van) and MgCO3 into the PAA hydrogel coating on the SIS extracellular matrix substrate, a dual-functional material with strong antibacterial (antibacterial efficiency of 99.17%) and pro-angiogenic (3.47 times higher than the control group) properties was constructed. The material exhibited sufficient bursting strength (20.50 kPa) to effectively seal dura mater injuries and prevent CSF leakage. In vivo animal experiments using dura mater injury models in rats, rabbits and beagles further confirmed the significant therapeutic potential of the biological patch, emphasizing its prospect as a multifunctional and effective solution for future neurosurgical applications.
[0215] It should be noted that, although the technical solutions of the present disclosure are introduced with specific examples, those skilled in the art will appreciate that the present disclosure should not be limited thereto.
[0216] The embodiments of the present disclosure have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. An asymmetric adhesive biological patch, characterized in that: include: A substrate having a fiber structure, and An adhesive layer, the adhesive layer is derived from an adhesive composition, the adhesive composition includes a monomer, a photoinitiator and a crosslinking agent, and, The adhesive composition further comprises an antibiotic compound and / or a component providing active metal ions.
2. The asymmetric adhesive biological patch according to claim 1, characterized in that: Based on 100% of the total weight of the adhesive composition, the content of the antibiotic compound is 0.1%-3%, and / or the content of the component providing active metal ions is 1%-10%.
3. The asymmetric adhesive biological patch according to claim 1 or 2, characterized in that: The active metal ions include one or a combination of two or more of magnesium ions, copper ions, calcium ions, manganese ions, zinc ions, chromium ions, cobalt ions, strontium ions, and iron ions; and / or, The antibiotic compound includes one or a combination of two or more of penicillins, cephalosporins, erythromycin, lincomycin, clindamycin and vancomycin.
4. The asymmetric adhesive biological patch according to any one of claims 1 to 3, characterized in that: Based on 100% of the total weight of the adhesive composition, the content of the monomer is 70%-97%, the content of the photoinitiator is 0.2%-5%, and the content of the crosslinking agent is 1%-10%.
5. The asymmetric adhesive biological patch according to any one of claims 1 to 4, characterized in that: The monomers include acrylic acid monomers and / or acrylamide monomers; preferably include one or a combination of two or more of acrylic acid, polyacrylamide, polyacrylic acid, and polyhydroxyethyl methacrylate; and / or, The cross-linking agent includes one or a combination of two or more of methacrylated gelatin, methacrylated hyaluronic acid, polycaprolactone diacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and N,N-methylenebisacrylamide; and / or, The photoinitiator includes a ketone photoinitiator, preferably including one or a combination of two or more of α-ketoglutaric acid, 2,2-dimethoxy-2-phenylacetophenone, α-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and 2-hydroxy-2-methyl-1-phenyl-1-propanone.
6. The method for preparing the asymmetric adhesive biological patch according to any one of claims 1 to 5, characterized in that: The method comprises the steps of composite-molding the adhesive layer and the substrate.
7. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: a step of obtaining an adhesive composition; The adhesive composition is present on at least one surface of the substrate, and an asymmetric adhesive biological patch is obtained after chemical reaction.
8. The preparation method according to claim 6 or 7, characterized in that: The adhesive composition is dissolved in a solvent to form a prepolymerization solution, and the prepolymerization solution is present on at least one surface of the substrate.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The reaction conditions include being carried out under the irradiation of ultraviolet light; preferably, the power of the ultraviolet light is 200-400W, and the irradiation time is 25-40 minutes.
10. Use of the asymmetric adhesive biological patch according to any one of claims 1 to 5 for preparing tissue repair products, in particular for preparing dura mater repair materials, skull repair materials, and postoperative defect repair materials.
Citation Information
Patent Citations
Biological tissue matrix material, and preparation method and purpose thereof
CN107007886A
Cited By
Self-adhesive biological patch as well as preparation method and application thereof
CN121313914A